Багаторівнева модель захисту пристроїв Інтернет речей - Печенюк, Максим Олегович (Тернопіль, ЗУНУ, 2025)
Метою роботи є розробка та демонстрація прототипу багаторівневої моделі захисту пристроїв Інтернету речей, яка забезпечує комплексний підхід до протидії кіберзагрозам на всіх рівнях IoT-архітектури з урахуванням специфічних обмежень та вимог цих систем. The aim of the work is to develop and demonstrate a prototype of a multilayer security model for IoT devices, providing a comprehensive approach to countering cyber threats at all levels of IoT architecture, taking into account the specific limitations and requirements of these systems.
Multilayer Security Model for Internet of Things Devices
Keywords: IoT; інтернет речей; кібербезпека; захист інформації; криптографія; виявлення вторгнень; машинне навчання; Zero Trust; nternet of things; cybersecurity; information protection; cryptography; intrusion detection; machine learning